Pengaruh Penjualan, Harga Pokok Penjualan, Biaya Operasional dan Pendapatan Lain-Lain Terhadap Laba Bersih pada PT. Pesona Minuman Indonesia Tahun 2021-2023 - Suroso Suroso (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
Net profit is an important indicator in assessing a company's financial performance because it reflects the effectiveness of management in generating profits. Several factors that influence net profit include sales, cost of goods sold, operating expenses, and other income. This study aims to analyze the influence of these factors on net profit at PT. Pesona Minuman Indonesia during the 2021–2023 period. The independent variables include sales, cost of goods sold, operating expenses, and other income, while net profit serves as the dependent variable. A quantitative approach using multiple linear regression was applied to 36 quarterly data from the company. The results show that sales, cost of goods sold, and operating expenses have a positive and significant influence on net profit, while other income has a negative and significant influence. Simultaneously, all four variables have a significant influence on the company's net profit. This finding emphasizes the importance of good management of sales and operating costs as key factors in achieving optimal profitability. Therefore, the company needs to focus on increasing sales and controlling operating costs to maximize its net profit.